Co-Operative Movement & Prudential Norms in Co-Operative Banks: Exploring the Role of Co-Operative Banks in Economic Development (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Banking is one of the key sectors of the economy. Its energy and vitality indicate the health and prosperity of any nation. Banking institution plays a pivotal role in the development of the economy by financing the requirements of trade, industry and agriculture with higher degree of contribution and responsibility. Thus, the development of country is integrally linked with development of banking. Co-operative Banks also occupy an important place in nation’s banking system. If one goes through the evolutionary stage of man’s history, he will find that cooperative action of some sort had already existed. In fact, it is as old as civilization because without voluntary co-operation of the individuals in a community it would be almost impossible to raise the standard of the family, group or tribe above the subsistence level. Co-operation refers to voluntary association, which is formed on the basis of equality and for some common purposes. The basic principle of the co-operation is “Each for all and all for each”. Co-operation as a system has found favour with almost all political parties and economic system all over the world as it offers unlimited opportunities for the people to participate in the economic resurgence especially in developing countries, the establishment and growth of co-operative is looked up, as an effective vehicle for the economic, social and cultural development of its inhabitants.